Variation in Transfusion Practice and How to Influence Clinicians' Use of Blood in Hospitals - Stanworth, S; Francis, J; Murphy, M; Tinmouth, A (John Wiley and Sons, 2013)
Blood components are scarce and costly resources that are required for almost every area of hospital practice. Most quality improvement activity in transfusion has centred on small incremental improvements in safety of donated blood for transfusion, although increasing attention is now focusing on improving blood use by clinicians to be consistent with evidence-based recommendations. Audits of transfusion provide information on (variable) compliance with standards and levels of unnecessary transfusions and findings continue to show unnecessary use of blood outside established guidelines. The translation of research findings into hospital practice is often slow and haphazard and this applies to transfusion as well as other branches of healthcare. Many different interventions are undertaken by hospitals to change transfusion practice, but there are real uncertainties about their effectiveness and durability. There is a need for research to define the determinants of transfusion behaviour to guide the design and selection of interventions better in order to deliver optimal change in transfusion practice. This edition first published 2013 © 2001, 2005, 2009, 2013 John Wiley and Sons Ltd.